THE EFFECT OF THE PROVISION OF BPJS-HEALTH EDUCATION AND TRAINING ON THE USE OF THE MOBILE-JKN APPLICATION - Rizky Chaeraty Syam; Auliyah Nurazizah; Novena Maylania; Nur Afifah Irwan; Karmila Wahyuni; Nur Hilmi Dwiadirah (Universitas Islam Negeri Alauddin Makassar, 2022)
Background: One form of health policy from the government is the national health insurance system and at this time BPJS-Health has launched a Mobile JKN application which is an innovation to make it easier for participants to manage BPJS Health and aims to facilitate the community towards prosperity. In the Sanrobone village, Sanrobone sub-district, Takalar district, the target and achievement of using BPJS-Health is still very far from what is expected, due to the large number of inactive community BPJS and the lack of public understanding of the BPJS-Health system and the community does not understand how to use the Mobile JKN application. Purpose: This activity is carried out to increase public understanding and participation in BPJS-Health services in Sanrobone Village, Sanrobone District, Takalar Regency. Method: This activity is carried out in several stages, namely the preparation stage, the implementation stage and the evaluation stage. The evaluation was carried out using a pre-post test questionnaire which was distributed to participants. The data analysis technique used is the Wilcoxon test. Results: The results showed that BPJS-health counseling was able to increase the knowledge of cadres in Sanrobone Village, Sanrobone District, Takalar Regency. Conclusion: BPJS-health counseling in Sanrobone Village, Sanrobone District is considered to have met the indicators of success because there was an increase in respondents' knowledge after counseling.